HR Competency Challenges in Developing Marketing Strategies: A Bibliometric Review - Loso Judijanto; Erri Wahyu Puspitarini; Agung Zulfikri (West Science Interdisciplinary Studies, 2024)
In today's dynamic business landscape, the synergy between human resources (HR) and marketing strategies is pivotal for organizational success. This bibliometric review investigates the challenges encountered by HR professionals in contributing to the development of effective marketing strategies. By analyzing 980 research papers published between 1981 and 2024, this study highlights the substantial impact of HR competencies on marketing strategy formulation and implementation. The analysis identifies key thematic clusters, influential literature, and emerging trends, shedding light on areas for future research and managerial practice. Findings emphasize the importance of aligning HR strategies with broader organizational goals and adapting to evolving market dynamics to foster sustainable business success.